2012
DOI: 10.1002/hed.22960
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis: Role in locally aggressive biological behavior of ameloblastoma and keratocystic odontogenic tumor

Abstract: The results suggest that tumor angiogenesis may play an important role in locally invasive aggressive biologic behavior of ameloblastoma and keratocystic odontogenic tumor. The angiogenesis could be a potent target for developing antiangiogenic therapeutic strategies, particularly in recurrent cases of odontogenic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
2
8
0
1
Order By: Relevance
“…The contents of the MRC have been reported to consist of branches of inferior alveolar vessels and nerves ( 1 , 17 ). Histopathological surveys confirm the presence of myelinated nerve fibres associated with numerous venules and an artery ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of the MRC have been reported to consist of branches of inferior alveolar vessels and nerves ( 1 , 17 ). Histopathological surveys confirm the presence of myelinated nerve fibres associated with numerous venules and an artery ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular retromolar canal (MRC) is a rare anatomic variation found in the retromolar triangle, a small triangular-shaped region posterior to the third molar tooth in the mandible ( 1 ). Identifying the position and configuration of mandibular canal variations are important in surgical procedures including sagittal split osteotomy, removal of impacted third molars, and implant placement ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compelling data implicate angiogenesis and tumor‐associated neovascularization as a central pathogenic step in the process of tumor growth and invasion []. Our immunohistological examination of this odontogenic myxofibroma clearly revealed that CCN2 was highly expressed in microvascular endothelial cells and in the surrounding tumor cells.…”
Section: Discussionmentioning
confidence: 78%
“…21,22 This complex process, which can be measured by determining the angiogenic index with antibodies against endothelial cell epitopes such as CD34, has been recognized as an important event in the development and progression of odontogenic cysts and tumors, including KOTs. 23,24,25 Although a crucial process in tumor progression, angiogenesis may not accompany the growth of tumor cells, with the consequent emergence of hypoxic areas in the tumor, a fact particularly highlighted in the case of malignant tumors. 26,27 In this respect, neoplastic cells increase the uptake and metabolism of glucose in order to adapt to and survive under the hypoxic conditions of the microenvironment.…”
Section: Introductionmentioning
confidence: 99%